PENGUJIAN SECARA SIMULTAN DAN PARSIAL PENDAPATAN ASLI DAERAH (PAD) DAN DANA PERIMBANGAN TERHADAP BELANJA MODAL - Padriyansyah Padriyansyah; Muhammad Said (Universitas Tridinanti, 2021)
The objectives of this study are: 1) to determine and analyze the effect of local original income and balancing funds simultaneously on capital expenditures in the Palembang City Government, 2) to determine and analyze the effect of partial local revenue and balancing funds on capital expenditures in the City Government Palembang. The population is the report of local revenue, balancing funds and capital expenditures in the Palembang City Government APBD. While the sample is local revenue, balancing funds and capital expenditures in the Palembang City government for a month for 3 years (36 months) from 2015 to 2017 using the purposive sampling method.The research technique is carried out by using multiple regression analysis model which aims to find out and obtain an overview of how much influence the independent variable has on the dependent variable. The results of the study are partially accepted, H1 means that local revenue has an effect on capital expenditure. H2 is accepted, meaning that the balancing fund partially affects capital expenditures, while simultaneously H3 is accepted, meaning that regional original income and balancing funds simultaneously affect capital expenditures.Keywords: local revenue, balancing fund, capital expenditure